Managing the Self: Lessons from the Bhagavad Gita on Personal Management and Development - Hegde, Kavya P.; Nayak, Venkatesha (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
This study delves into the key principles of the Bhagavad Gita pertaining to personal management and development, assessing their applicability in contemporary practices. Utilizing a textual analysis approach alongside an extensive review of relevant literature, the study examines the Gita’s teachings on detachment, expertise in action, self-discipline, and spiritual consciousness—all crucial aspects of personal management and development. For individuals and organizations seeking effective personal management and development, To integrate these principles into daily routines, the study suggests structured reflection practices, goal-setting frameworks, and leadership training programs that emphasize ethical decision-making and mindfulness. Ultimately, the study concludes that adopting these timeless principles can cultivate a work culture grounded in respect, compassion, and holistic well-being.